Effects of lumacaftor/ivacaftor on cystic fibrosis disease progression in children 2 through 5 years of age homozygous for F508del-CFTR: a phase 2 placebo-controlled clinical trial - Stahl, Mirjam; Roehmel, Jobst; Eichinger, Monika; Doellinger, Felix; Naehrlich, Lutz; Kopp, Matthias V.; Dittrich, Anna-Maria; Lee, Christopher; Sommerburg, Olaf; Tian, Simon; Xu, Tu; Wu, Pan; et al. (Annals of the American Thoracic Society, 2023)
Lumacaftor/ivacaftor (LUM/IVA) was shown to be safe and well tolerated in children 2 through 5 years of age with cystic fibrosis (CF) homozygous for F508del-CFTR in a Phase 3 open-label study. Improvements in sweat chloride concentration, markers of pancreatic function, and lung clearance index2.5 (LCI2.5), along with increases in growth parameters, suggested the potential for early disease modification with LUM/IVA treatment. To further assess the effects of LUM/IVA on CF disease progression in children 2 through 5 years of age using chest magnetic resonance imaging (MRI). ...